Standards based education in Egypt and Singapore - El Masri, Dara Akeal (AUC Knowledge Fountain, 2013)
Mathematics education is important for all members of modern societies. In Egypt, the importance of mathematics education needs greater emphasis because of its role in providing job opportunities and helping to understand and build new economies, as well as, reducing the gap between Egypt and other developing countries. In order to know the aspects that need improvement in the Egyptian mathematics educational system, this study analyzed both the national Egyptian and the national Singaporean eighth grade mathematics educational system; mainly the standards, curricula, and textbooks. The analysis of the standards was done by comparing them to the characteristics of high quality standards issued by the Asia Pacific Economic Cooperation (APEC TATF & USAID, 2009), as well as the flaws that should not be part of the standards (Marzano & Haystead, 2008), and whether they incorporate higher order thinking skills or not. The curricula and the textbooks were examined using the content analysis criteria set by Confrey and Stohl (2004). Afterwards, the extent of alignment between the standards, curricula, and textbooks was checked; based on Bakerâ s (2004) alignment analogies. The main results of this study showed that the national Egyptian standards do not fully comply with the six characteristics of high quality standards, are not completely flawless, and need more incorporation of higher order thinking skills. As for the curriculum and the textbook, they need a number of improvements. The problem with the curriculum is that it is very brief and only lists the names of the lessons to be taught and their corresponding dates. As for the textbook, the main aspects that weaken it are that it does not incorporate higher order thinking skills, connections between topics, real world and interdisciplinary connections, and relations to studentsâ previous experiences. Moreover, it has some major spelling mistakes and errors in model answers. As for the national Singaporean curriculum framework, it complies with five of the six characteristics of high quality standards, is flawless, and is centered around problem solving. When considering the Singaporean textbook, it has several strengths, the objectives and learning outcomes are clearly stated, the material is presented in a comprehensive manner, and the exercises and assessments progress from being simple and direct to hard and challenging. In addition, higher order thinking skills are incorporated in all aspects of the textbook and no major mistakes were observed. Another important strength is that real world connections are incorporated in all topics. A set of recommendations was given at the end of the study based on the results of the national Singaporean educational system results, with regards to those that need improvement in the Egyptian eighth grade mathematics educational system.